2022
DOI: 10.21203/rs.3.rs-1049912/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prophylactic Clip Closure for Mucosal Defects is Associated with Reduced Adverse Events After Colorectal Endoscopic Submucosal Dissection: A Propensity-Score Matching Analysis

Abstract: Background: Whether prophylactic endoscopic closure after colorectal endoscopic submucosal dissection (ESD) reduces the risk of postoperative adverse events remains unclear due to variabilities in lesion characteristics. Therefore, we conducted a retrospective study using propensity-score matching to evaluate the efficacy of prophylactic clip closure in preventing postoperative adverse events after colorectal ESD. Methods: This single-center retrospective cohort study included 219 colorectal neoplasms which we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Compared to diagnostic procedures, AE occurred more frequently during or after therapeutic procedures (n=9 (17,3%) vs n=43 (84,6%) respectively). to all endoscopy procedures or anaesthesia in endoscopy (16)(17)(18). These differences in recording (all vs specific endoscopic procedures / retrospective vs prospective / voluntary vs systematic review of medical files / early vs late AE) may lead to a wide variation in reported AE rates, as encountered in the literature (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to diagnostic procedures, AE occurred more frequently during or after therapeutic procedures (n=9 (17,3%) vs n=43 (84,6%) respectively). to all endoscopy procedures or anaesthesia in endoscopy (16)(17)(18). These differences in recording (all vs specific endoscopic procedures / retrospective vs prospective / voluntary vs systematic review of medical files / early vs late AE) may lead to a wide variation in reported AE rates, as encountered in the literature (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the rate of delayed bleeding was 1.2 %. This is notable given recent studies that have suggested the role of prophylactic defect closure in possibly reducing the rate of delayed post-ESD bleeding [5,9]. Several studies have identified risk factors for delayed bleeding after colorectal ESD.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal delayed AE rate (1.2 %) after prophylactic closure using TTS sutures ± TTS clips is noteworthy and suggests secure defect closure. Similarly, TTS clip monotherapy for closure of a large mucosal defect after colorectal ESD has demonstrated a delayed bleeding rate of 0-6 % and a delayed perforation rate of 0 % [4,5]. Large prospective studies are needed to confirm the efficacy of TTS sutures in the prevention of post-ESD bleeding.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation